2018
DOI: 10.5194/tc-12-25-2018
|View full text |Cite
|
Sign up to set email alerts
|

Frazil-ice growth rate and dynamics in mixed layers and sub-ice-shelf plumes

Abstract: Abstract. The growth of frazil or granular ice is an important mode of ice formation in the cryosphere. Recent advances have improved our understanding of the microphysical processes that control the rate of ice-crystal growth when water is cooled beneath its freezing temperature. These advances suggest that crystals grow much faster than previously thought. In this paper, we consider models of a population of ice crystals with different sizes to provide insight into the treatment of frazil ice in large-scale … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…These laboratory measurements of the properties of frazil ice particles and flocs in saline water can be applied to oceanic frazil ice production models (Galton-Fenzi et al, 2012;Wells, 2015 and2018). Due to the complexity of the processes involved in the frazil ice production, all these models rely on the parameterization of small-scale phenomena and on the introduction of empirical constants (De Santi and Olla, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These laboratory measurements of the properties of frazil ice particles and flocs in saline water can be applied to oceanic frazil ice production models (Galton-Fenzi et al, 2012;Wells, 2015 and2018). Due to the complexity of the processes involved in the frazil ice production, all these models rely on the parameterization of small-scale phenomena and on the introduction of empirical constants (De Santi and Olla, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the complexity of the processes involved in the frazil ice production, all these models rely on the parameterization of small-scale phenomena and on the introduction of empirical constants (De Santi and Olla, 2017). Rees Jones and Wells (2018) noted that it is difficult to discriminate between models that use different crystal growth rate parameterizations because they can predict the same experimentally observed supercooling time series using different size distributions of initial seed crystals. They concluded that what was needed to discriminate between different models was for experiments to be conducted to measure crystal sizes as well as supercooling, which is precisely what we have done in this study.…”
Section: Discussionmentioning
confidence: 99%
“…where the one-to-one equivalence has no dynamic significance). Rees Jones and Wells (2018) use one of the faster rise rates from the same set of results which is applicable to smaller crystal sizes (e.g. none of which conforms to the drag based estimates described in Daly, 1984) whereas Matsumura and 305 Oshima (2015) use a fixed rise rate of 1 mm s -1 , again for small crystals.…”
Section: Is There Evidence Of Large Pelagic Crystals?mentioning
confidence: 99%
“…Inclusion of suspended frazil in ocean modeling is well developed (e.g., Jenkins & Bombosch, 1995; Svensson & Omstedt, 1998). Plume models include a range of frazil crystal size classes (e.g., Holland & Feltham, 2005; Hughes et al, 2014; Rees Jones & Wells, 2018; Smedsrud & Jenkins, 2004). Frazil crystal size distribution is also now included in three‐dimensional ocean circulation models (Galton‐Fenzi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%